Mindfulness trait and the potential mediating role of emotional regulation strategies in bipolar disorder. - Burgos-Julián, Francisco A.; Díaz-Silveira, Cintia; Ruíz-Íñiguez, Raquel; Santed Germán, Miguel A. (Anales de Psicología / Annals of Psychology, 2024)
This cross-sectional study investigates the association between the main symptoms of Bipolar disorder (BD) and emotional regulation difficulties in adaptive and maladaptive emotional regulation strategies (ERS). In addition, this study examines the possible mediating effects of ERS with dispositional mindfulness and bipolar symptoms. Method. Twenty-four adults diagnosed with BD completed the Mindful Attention Awareness Scale (MAAS), the Beck Depression Inventory (BDI-II), the Altman Mania Self-Assessment Scale (ARSM), the Trait Anxiety Inventory (STAI-R), and the Cognitive Emotional Regulation Questionnaire (CERQ). Results. First, multiple regression analysis showed how depression was significantly positively related to self-blame, whereas trait anxiety was positively associated with self-blame and catastrophizing. Second, the results of the mediation analysis have shown a significant mediation effect for the self-blame in the relationship between mindfulness and depression (a*b = -.15; BCI 95% [-.36, -.03]) and between mindfulness and trait anxiety (a*b = -.09; BCI 95% [-.27, -.01]). Conclusions. Our results report the role of self-blame and catastrophizing in BD and how these might significantly mediate between dispositional mindfulness and symptoms of depression and anxiety. These results suggest that a meditation practice focused on reducing catastrophizing and self-blame may be especially helpful for symptoms of depression and anxiety in bipolar patients.